Aplicación del principio de celeridad en los procedimientos para acceder a beneficios penitenciarios en el Centro de Privación de Libertad del cantón Guaranda. - Gaibor García, Alejandro Javier (2023)
The Ecuadorian penitentiary system is currently going through a large-scale crisis, for this reason it is considered the option of applying penitentiary benefits, which contribute to improve the quality of life of the PPL and ensure greater stability and security within the prisons of Ecuador, for this reason this research aims to determine the importance of the principle of celerity in the procedure to access the penitentiary benefit of the PPL in the Center of Deprivation of Liberty of the Guaranda canton. In order to achieve this, the methodology used is descriptive-correlational, since it specifies and delineates the basic characteristics of the study problem, establishing the properties, characteristics, profiles and behaviors of the Ecuadorian penitentiary system, in correspondence with the benefits of the PPL. Among the main findings that were found is that the penalty is considered as a preventive function, through which it seeks to achieve the rehabilitation and reintegration of the prisoner into society; however, the process to access the regimes, take months to be resolved by the competent authorities, which produces a significant delay, especially in the issuance of reports by the departments of evaluation and diagnosis, a fact that violates the principles of speed and reasonable time. Key words: principle of celerity, penitentiary system, prison benefits, open regime.